The role of local government in supporting the development of the MSMEs sector in the society 5.0 - Toman Sony Tambunan; Ida Royali; Dessy Julia; M. Iman Hidayat (Institute of Computer Science (IOCS), 2023)
This research aims to analyze the role of Regional Government in supporting Micro, Small and Medium Enterprises (MSMEs) to advance to class in Medan City. The research method used is a qualitative descriptive research approach. This research focuses on the role of Regional Government in developing Micro, Small and Medium Enterprises (MSMEs) to advance to class in Medan City. Data collection techniques through observation, in-depth interviews and documentation review. Research data analysis used the Miles and Huberman model, and the data validity test was carried out based on trustworthiness criteria. The results of the research show that in developing MSMEs in Medan City, the Medan City Department of Cooperatives, Small and Medium Enterprises, Industry and Trade has carried out its role well. This is proven through support for the progress of Micro, Small and Medium Enterprises (MSMEs) by providing capital assistance; assistance in processing business permits and product certification; supporting digitalization-based business management; as well as supporting e-commerce based marketing activities. The results of this research can be used by the Government as a reference for optimizing the regional Micro, Small and Medium Enterprises sector to become a class based on Law of the Republic of Indonesia Number 20 of 2008.